2019
DOI: 10.1080/00987913.2019.1624909
|View full text |Cite
|
Sign up to set email alerts
|

Leaning into Browser Extensions

Abstract: An array of browser extensions have been developed to help researchers locate full-text content, whether that full text is available in an institutional repository, on a publishers site, or in an open access journal. Examples of such browser extensions include Unpaywall, Kopernio, EZproxy tools, and Lean Library. This Balance Point column focuses on the growth of browser extensions, the need they are filling, and their adoption by libraries. Particular attention is paid to the Lean Library browser extension an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…It was also observed that plugins do not remain consistent with their approach and availability. Regarding phased withdrawal of the once highly used plugins such as LibX (a chrome and firefox plugin) and Open URL Referer (a Firefox plugin) by many libraries, Ferguson (2019) reasoned the lack of availability of necessary support for updated versions of those plugins by many libraries regularly. The link resolver plugin improves the link with the full-text resources.…”
Section: Other Pluginsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also observed that plugins do not remain consistent with their approach and availability. Regarding phased withdrawal of the once highly used plugins such as LibX (a chrome and firefox plugin) and Open URL Referer (a Firefox plugin) by many libraries, Ferguson (2019) reasoned the lack of availability of necessary support for updated versions of those plugins by many libraries regularly. The link resolver plugin improves the link with the full-text resources.…”
Section: Other Pluginsmentioning
confidence: 99%
“…Browser plugins, particularly those simplifying the process of searching and finding the pdf of a full-text article, have been summarized discretely (Ferguson, 2019; Hoy, 2019; Joseph et al , 2019; Heady, 2021). Focusing on academic search plugins, Hoy (2019) identified two types plugins- active and passive.…”
Section: A Review Of Pluginsmentioning
confidence: 99%